Monitoring the photosystem II behavior of wild and cultivated barley in response to progressive water stress and rehydration using OJIP chlorophyll a fluorescence transient. (2nd July 2016) - Ghotbi-Ravandi, Ali Akbar; Shahbazi, Maryam; Pessarakli, Mohammad; Shariati, Mansour
ABSTRACT: To study the effects of progressive drought stress on photosystem II behavior of wild type (Spantaneum) and cultivated barley (Morocco), different levels of soil water availability, including control, moderate, mild, and severe water stress (70%, 50%, 30%, and 10% water holding capacity of soil, respectively) and rehydration were used. Polyphasic OJIP fluorescence transient of Morocco plants exhibited a considerable increase in fluorescence intensity at O, J, and I steps under mild and severe stress relative to slight increase in wild barley. Values of fluorescence parameters and quantum efficiencies, including minimal fluorescence, relative variable fluorescence at phase J and I, maximal quantum yield of photosystem II (PSII), performance index, electron transport yield, and excitation transfer efficiency were influenced by water stress in both genotypes. These parameters were significantly less affected in wild type barley by progressive drought stress compared to Morocco. After re-watering, both genotypes were able to restore from severe drought in most of the traits. Based on our findings, highly correlated values of relative water content (RWC) and independent JIP-test parameters (P < 0.01) indicate that the chlorophyll a fluorescence induction technique is sensitive to plant water status and performance index represent an accurate and reliable indicator for early stress detection and also explore plant vitality under water stress.